Baseball for young champions - Antonacci, Robert Joseph, 1916- 4 0 16; 1925- Barr, Jene.;Boyd, Patti,;Berra, Yogi; 5 (New York : McGraw-Hill, 1977)
Basic instruction in the skills of baseball--pitching, catching, and fielding--as well as in selecting adequate equipment and keeping scores and records.
Includes index.
Booklist
5-8;5-8
Keywords: 2 -- 0; 6; Baseball;Baseball.;Baseball. -- Juvenile literature; 20; 2